2019
DOI: 10.1242/dmm.037903
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a zebrafish hematological disease model induced by 1,4-benzoquinone

Abstract: Benzene exposure is associated with various hematological disorders, in particular leukemia. The reactive metabolite of benzene, 1,4-benzoquinone (BQ), generated in bone marrow, is suggested to be a key molecule in mediating benzene-induced hematotoxicity and carcinogenicity. However, its pathogenic role remains largely unknown due to a lack of suitable vertebrate whole-organism models. Here, we present an in vivo study to reveal the effect of BQ exposure on hematotoxicity in zebrafish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although many countries have established the occupational exposure limit for benzene to reduce the harm mediated by it, exposure to benzene concentrations below the USA occupational standard of 1 part per million can cause hematotoxic effects such as reduced erythrocytes, leucocytes, and thrombocytes (Lan et al, 2004; Schiffman et al, 2018). The benzene metabolite, 1, 4‐benzoquinone (1,4‐BQ), is produced in the bone marrow and considered to be one of the major substances mediating hematotoxicity (Zhang et al, 2019). Studies have found that 1,4‐BQ affects mitochondria function, ultimately leads to reactive oxygen species (ROS)‐dependent cell apoptosis (Das et al, 2010; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many countries have established the occupational exposure limit for benzene to reduce the harm mediated by it, exposure to benzene concentrations below the USA occupational standard of 1 part per million can cause hematotoxic effects such as reduced erythrocytes, leucocytes, and thrombocytes (Lan et al, 2004; Schiffman et al, 2018). The benzene metabolite, 1, 4‐benzoquinone (1,4‐BQ), is produced in the bone marrow and considered to be one of the major substances mediating hematotoxicity (Zhang et al, 2019). Studies have found that 1,4‐BQ affects mitochondria function, ultimately leads to reactive oxygen species (ROS)‐dependent cell apoptosis (Das et al, 2010; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…erythrocytes, leucocytes, and thrombocytes (Lan et al, 2004;Schiffman et al, 2018). The benzene metabolite, 1, 4-benzoquinone (1,, is produced in the bone marrow and considered to be one of the major substances mediating hematotoxicity (Zhang et al, 2019).…”
mentioning
confidence: 99%
“…Improved genome annotation, ease of husbandry and the development of genome editing (see, for example, Prykhozhij and Berman, 2018), xenotransplantation (Parada-Kusz et al, 2018) and imaging tools have helped propel the zebrafish to the forefront of hematopoiesis modeling (reviewed in Konantz et al, 2019). Indeed, zebrafish models have informed the basis for malignant transformation in the hematopoietic niche (Zhang et al, 2019;Gjini et al, 2019). In parallel, isogenic cell line pairs that allow researchers to model hematopoiesis and interrogate the precise functional consequences of disease-causing mutations can now be produced using genome editing in patient-derived iPSCs (reviewed in Georgomanoli and Papapetrou, 2019).…”
Section: Introductionmentioning
confidence: 99%